FGF21 induced by carbon monoxide mediates metabolic homeostasis via the PERK/ATF4 pathway. Issue 5 (2nd January 2018) - Joe, Yeonsoo; Kim, Sena; Kim, Hyo Jeong; Park, Jeongmin; Chen, Yingqing; Park, Hyeok‐Jun; Jekal, Seung‐Joo; Ryter, Stefan W.; Kim, Uh Hyun; Chung, Hun Taeg
Abstract : The prevalence of metabolic diseases, including type 2 diabetes, obesity, and cardiovascular disease, has rapidly increased, yet the molecular mechanisms underlying the metabolic syndrome, a primary risk factor, remain incompletely understood. The small, gaseous molecule carbon monoxide (CO) has well‐known anti‐inflammatory, antiproliferative, and antiapoptotic effects in a variety of cellular‐ and tissue‐injury models, whereas its potential effects on the complex pathways of metabolic disease remain unknown. We demonstrate here that CO can alleviate metabolic dysfunction in vivo and in vitro. We show that CO increased the expression and section of the fibroblast growth factor 21 (FGF21) in hepatocytes and liver. CO‐stimulated PERK activation and enhanced the levels of FGF21 via the eIF2a‐ATF4 signaling pathway. The induction of FGF21 by CO attenuated endoreticulum stress‐ or dietinduced, obesity‐dependent hepatic steatosis. Moreover, CO inhalation lowered blood glucose levels, enhanced insulin sensitivity, and promoted energy expenditure by stimulating the emergence of beige adipose cells from white adipose cells. In conclusion, we suggest that CO acts as a potent inducer of FGF21 expression and that CO critically depends on FGF21 to regulate metabolic homeostasis.—Joe, Y., Kim, S., Kim, H. J., Park, J., Chen, Y., Park, H.‐J., Jekal, S.‐J., Ryter, S. W., Kim, U. H., Chung, H. T. FGF21 induced by carbon monoxide mediates metabolic homeostasis via the PERK/ATF4 pathway. FASEB J. 32, 2630–2643 (2018). www.fasebj.org